N-(2-Chlorophenyl)-2-nitrobenzenesulfonamide - Chaithanya, U. (International Union of Crystallography, 2012)
In the title compound, C(12)H(9)ClN(2)O(4)S, the N—H bond in the –SO(2)—NH– segment is syn to both the ortho-nitro group in the sulfonylbenzene ring and the ortho-Cl atom in the aniline ring. The molecule is twisted at the S—N bond with a torsion angle of 75.0 (2)°. The dihedral angle between the sulfonylbenzene and aniline rings is 54.97 (11)°. The amide H atom shows bifurcated hydrogen bonding, generating S(7) and C(4) motifs. In the crystal, N—H⋯O(S) hydrogen bonds link the molecules into chains.